RACISM IN SUBURBICON BY GEORGE CLOONEY - Endra Muhammad Radi; Yosep Bambang Margono (Universitas 17 Agustus 1945 Semarang, 2022)
In this research I discuss about racism in Suburbicon film by George Clooney (2017). The reason I analyze racism are because I realize that racism does not start from the environment, but racism starts with the people themselves and we should know more about racism, including its definition, the history, the impact, the causes of racism and the struggle of black people who experienced racism. The main theory that I used is the extrinsic approach to Literature: Literature and Society. The method that I used is qualitative descriptive. The result found that racism benefits the perpetrators which are superior, but it harms the victims of racism which are the inferior because the victim suffers a loss in the form of mental and physical. The concept of racism is a concept that distinguishes one race from another and considers one race to be superior to other races. Racism can occur because of differences. In this thesis, I conclude that there are three factors that cause racism. The first is because of the stereotypes in society. The second is because of an incident that happened to the Gardner Lodge family. The third is because of a lack of understanding of the meaning of difference. In addition, there are also impacts and consequences of the occurrence of racism in the Suburbicon film. The first is inequality. The second is divided into two, namely from the side of the race that benefits and the race that is harmed. On the one hand, racism brings “advantages” to the ruling race but on the other hand racism causes invaluable “losses” both mentally and physically for the harmed race. Keywords: Racism, Representation, Literature, Society, Film